2018
DOI: 10.1002/ldr.3181
|View full text |Cite
|
Sign up to set email alerts
|

Sunflower (Helianthus annuus L.) harvest: Tractor and grain chaser traffic effects on soil compaction and crop yields

Abstract: Previous studies have defined compaction as an important degradation process of agricultural soils. However, there is very little information (under field conditions) on the effects of tractor and grain chaser traffic during harvest operations on soil cropped for 15 years under no‐till cultivation methods. The aim of this study was to quantify the effects of two different total loads of tractor and grain chaser traffic on soil physical properties and sunflower (Helianthus annuus L.) yields. The treatments incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
9
0
3
Order By: Relevance
“…However, in the same reference period, the impact of mechanization on agriculture was also investigated. Particularly, some studies focused on soil compactness due to machinery traffic, which is a major concern in both agriculture and forestry mechanization activities [99][100][101][102][103][104]. Among them, Dalmis et al (2013) designed a chopper unit that can be installed under the header of a combine harvester and driven by via transmission chain connected to the header.…”
Section: Sunflower Mechanical Harvestingmentioning
confidence: 99%
“…However, in the same reference period, the impact of mechanization on agriculture was also investigated. Particularly, some studies focused on soil compactness due to machinery traffic, which is a major concern in both agriculture and forestry mechanization activities [99][100][101][102][103][104]. Among them, Dalmis et al (2013) designed a chopper unit that can be installed under the header of a combine harvester and driven by via transmission chain connected to the header.…”
Section: Sunflower Mechanical Harvestingmentioning
confidence: 99%
“…For these treatments (the combine harvester and the sprayer), the CI values were higher than 2500 KPa in the subsoil, (300 mm to 450 mm), denoting over-compaction. Also for these treatments, the CI exceeded the critical soil strength values, above which root growth and expansion are significantly affected (e.g., 11,14,18,19).…”
Section: Soil Water Content and Cone Indexmentioning
confidence: 97%
“…Besides, the treatments with the highest average ground pressure (combine harvester (> 135 kPa) and sprayer (> 233)) caused CI values exceeding 2000 kPa from the 0 mm depth level. Botta et al (2018b) suggested that this value is a limitation, not only of the seed emergence, but also for the root development. It is important to mention that Threadgill (1982) indicates that CI values above 1500 kPa decrease root development, while CI values of 2100 to 2500 kPa can stop root growth.…”
Section: Soil Water Content and Cone Indexmentioning
confidence: 99%
“…The adverse effects of soil compaction are visible not only in the arable layer. Deeper soil layers are also compacted, which can lead to the formation of plow pans that are very difficult to eliminate [17].…”
Section: Introductionmentioning
confidence: 99%